Systematics of Irvingiaceae and Ixonanthaceae (Malpighiales): phylogenetic analysis based on three plastid DNA loci - Byng, James W.; Bernardini, Benedetta; Christenhusz, Maarten J. M.; Chase, Mark W. (Phytotaxa, 2016)
Relationships of Ixonanthaceae and Irvingiaceae have been poorly known in the past. We therefore investigate the relationships of these families here. Plastid atpB, rbcL and ndhF sequences from taxa representing all genera were analysed using maximum likelihood. Allantospermum was found as sister to Irvingiaceae and does not belong to Ixonanthaceae where it was often traditionally placed. This position of Allantospermum in Irvingiaceae is further supported by numerous putative synapomorphic characters. Expanded species sampling in Ixonanthaceae found that African Phyllocosmus was embedded within a strongly supported clade containing American Ochthocosmus. A re-evaluation of morphological characters of the two supports an enlarged concept of Ochthocosmus. Within Irvingiaceae, the West African monotypic Desbordesia was embedded within a strongly supported clade of Old World Irvingia. These findings change circumscriptions of both Ixonanthaceae and Irvingiaceae.